ANALISIS SOSIAL DAN EKONOMI AGROFORESTRI BERBASIS TANAMAN SAGU (Metroxylon sagu): ALTERNATIF REHABILITASI HUTAN DAN LAHAN GAMBUT - Yanarita -; Afentina -; Sosilawaty -; C. Birawa -; Sri Monika (Lambung Mangkurat University-Indonesia, 2020)
Metroxylon sagu-based agroforestry can be an alternative pattern of rehabilitation of forests and peatlands. The study aimed to determine the social and economic aspects of Metroxylon sagu-based agro forestry activities in Pilang Village, Pulang Pisau Regency, Central Kalimantan. Pilang Village a village located in a peat area. The research methodis a survey method with interviews and questionnaires. Respondents as there search sample were farmers who were selected purposively along with as many as 40 people with the criteria of having an area of land > 0.25 ha and there were Metroxylon sagu plants. Data analysis uses descriptive qualitative and quantitative analysis for financial feasibility analysis (NPV and BCR). The results showed that socially Metroxylon sagu plant selection was determinedby: (1) hereditary (37.5%); (2) easy planting and maintenance (27.5%); (3) sourcesofincome (22%); and (4) others (12.5%). Metroxylon sagu-based agroforestry patterns can be distinguished by other types of vegetation, namely: (1) Metroxylon sagu, rubber and filler plants (32,5%); (2) Metroxylon sagu, rubber and wood (5%); (3) Metroxylon sagu, rubber, fruits and fill plants (20%); (4) Metroxylon sagu, fruit and plant fillings (42,5%). The contribution of Metroxylon sagu to Metroxylon sagu-based agroforestry revenuesis 7,63%. Based on commodity Metroxylon sagu, NPV value (5%) Rp102,464,359.8; (10%) Rp49,180,666.67; (15%) Rp47,0423,376.8 and BCR value (5%), (10%), (15%) is 23.47. Based on social and economic analysis, Metroxylonsagu-based agroforestry is recommended as an alternative to forest and peatland rehabilitation.